Analysis Of Vendor Performance Appraisal In The Airfreight Export Division Using The Analytic Hierarchy Process Method (Case Study: Dhl Global Forwarding Indonesia 2020) - Lira Agusinta; Apsada Juhri; Peppy Fahrial; Mohammad Wisanggeni Ariohadi (Politeknik APP Jakarta, 2024)
The purpose of this study was to determine the results of measurements of the priority vendors of the two vendors used by the company in the process of shipping export goods or shipment. This study uses the AHP-Likert Scale (Analytic Hierarchy Process) method where the Likert scale is used as a comparison. Problem solving is done by making research using qualitative research methodology with descriptive elaboration. Data collection is done by giving or making questionnaires to get the weight of the assessment carried out by inferring with AHP and Likert from the data collected through questionnaires shared where the respondents came from respondents who have dedication and direct links as well as have the capability to provide vendor performance assessments. The results of the research that were tested from the level of consistency were divided into 4 criteria, namely; Price, Service, Quality and Reliability and from the results of the qualitative calculation method by distributing questionnaires from 10 experts for two existing vendors, namely MSA Kargo and Andima, where MSA Kargo got a weight value of 22.84 and Andima got a weight value of 10.66.